2018
DOI: 10.20960/nh.1897
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and performance of top youth international male basketball players in Spanish national academy

Abstract: The “Century XXI” Project is a seven-year intervention sport program performed among the best Spanish youth basketball players, who were assigned to one of the following intervention groups based on the following criteria: age, position, mature level, and origin in the country. The study was performed (1996-2001) with a total of 90 players. The main purposes of this study were: a) to describe anthropometric and performance characteristics of top youth international male basketballers in the Spanish national ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 5 publications
5
15
0
7
Order By: Relevance
“…This study identified differences in anthropometrics’ factors and body composition, mainly in lean mass and BMI. This idea is in accordance with previous studies that confirmed it, and also added that the greatest changes occurred between Under 14–15 and Under 17 categories [ 44 ]. Regarding positions, it must be noted that from early ages there are morphological differences between centers and guards, which serve us as references to be able to select [ 44 ], although early specialization is not recommended.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study identified differences in anthropometrics’ factors and body composition, mainly in lean mass and BMI. This idea is in accordance with previous studies that confirmed it, and also added that the greatest changes occurred between Under 14–15 and Under 17 categories [ 44 ]. Regarding positions, it must be noted that from early ages there are morphological differences between centers and guards, which serve us as references to be able to select [ 44 ], although early specialization is not recommended.…”
Section: Discussionsupporting
confidence: 92%
“…This idea is in accordance with previous studies that confirmed it, and also added that the greatest changes occurred between Under 14–15 and Under 17 categories [ 44 ]. Regarding positions, it must be noted that from early ages there are morphological differences between centers and guards, which serve us as references to be able to select [ 44 ], although early specialization is not recommended. In addition, other variables analyzed such as functional movements showed dependency with the age category, as several studies have claimed in young and elite basketball players [ 44 , 45 ], though no differences were observed in the linear sprint or strength tests, with the exception of the vertical f–v profile.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although strength and conditioning coaches use various methods to develop neuromuscular factors in youth basketball players [24], no studies to date, as far as we know, have investigated the effects of flywheel training on strength and power attributes in young basketball players. It should be recognized that the continuation of habitual team sport practice during puberty was proven to induce substantial improvements in lower body strength per se, without additional resistance training performed [25].…”
Section: Introductionmentioning
confidence: 99%